2006
DOI: 10.1111/j.0021-8774.2006.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards the feeling of emergence

Abstract: Emergence is a multi-dimensional notion; the meanings it has acquired span the mythopoetic to the scientific, especially as found in complex systems. Examples of emergence in Navaho and Egyptian imagery underscore its diverse cultural origins and applications as well as suggesting an underlying archetypal quality to the core concept. A brief overview of the use of this term in science starting in the 17th century helps to locate the roots of modern emergent views in the philosophy of Leibniz. Jung's own use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 12 publications
(6 reference statements)
0
36
0
Order By: Relevance
“…The process represents a kind of social synchronization and coherence, much like two clocks separated in time and space that undergo changes approximately simultaneously. This has been most commonly called a synchronicity, when the causal relation between one individual with another or an external event is not immediately obvious and rationally known (Cambray, 2006). Nonetheless, there may still be causal connections that are unavailable to conscious awareness that determine and guide the outcome of interactive behavior in a coherent way; and that coherence could also be contributed to by causal factors in the larger environment.…”
Section: Discussionmentioning
confidence: 99%
“…The process represents a kind of social synchronization and coherence, much like two clocks separated in time and space that undergo changes approximately simultaneously. This has been most commonly called a synchronicity, when the causal relation between one individual with another or an external event is not immediately obvious and rationally known (Cambray, 2006). Nonetheless, there may still be causal connections that are unavailable to conscious awareness that determine and guide the outcome of interactive behavior in a coherent way; and that coherence could also be contributed to by causal factors in the larger environment.…”
Section: Discussionmentioning
confidence: 99%
“…Daniel Stern (2004) has discussed this in terms of the "moment of meeting" (p. 28), and Jungians have been applying this thinking to a host of theoretical and practical considerations (Cambray 2011;Cambray & Carter, 2004;Hogenson, 2009). In one paper Cambray (2006) explored the affective experience associated with the onset of emergence in the clinical setting and suggested that the primary emotion of surprise/startle/shock was central. This in turn may serve as a link in regaining access to the transformative potential of the numinous and may be the reason that a number of researchers in complexity have turned to questions of spiritual experience; for example, Stuart Kauffman's (2008) book Reinventing the Sacred: A New View of Science, Reason and Religion blends complexity science, especially that associated with life forms, with a new way into spirituality.…”
Section: International Journal Of Transpersonal Studies 82mentioning
confidence: 99%
“…There are evidences however, that Jung anticipated such a turn most noted in his phenomenological descriptive approach developed early in his career in his association test researches (see Austin, 2009;Vezzoli et al, 2007) and in his immanent critique of such emerging phenomena from the patient. For a contemporary application of this crucial insight, see Cambray, 2006;Cambray, Gaillard, Gibeault, Gastelumendi & Kast, 2011. 5.…”
Section: Notesmentioning
confidence: 99%